(untitled) (Communications in Computational Physics, 2020)
Molecular dynamics simulations are performed to study the supercritical mixing process of the n-dodecane/nitrogen binary system. Previous studies have shown the existence of supercritical phenomenon under certain conditions in modern propulsion systems such as diesel engines. However, the physical mechanisms and internal driving forces of this phenomenon are still not well understood. In this paper, we attempt to answer this question through simulating the diffusion and evaporation of gaseous nitrogen and liquid phase n-dodecane. It addresses under what conditions the supercritical transition phenomenon happens and what features the supercritical evaporation process has. A unique configuration is constructed to mimic the evaporation of an n-dodecane thin film in an open nitrogen environment under conditions ranging from subcritical to supercritical. The detailed structure of the liquid-vapor interface during the evaporating process is described and the evaporation rate and the interface thickness are estimated, which show differences between subcritical and supercritical evaporation. Results indicate that under relatively high pressure conditions, the liquid surface transitions into supercritical state, and the liquid-vapor interface expands significantly with vanishing surface tension, leading to a diffusion like mixing process. It is shown that the supercritical evaporation would happen under conditions that correspond to the in-cylinder conditions of a turbo-charged engine.